The Economic Ascent of the Hotel Business - Slattery Paul (Goodfellow Publishing, 2009)
This book is an essential reading for Hotel Executives, their Advisor and Investors as well as a vital resource for those studying the Hospitality Business. Economic Structure, Historic Agricultural Economies and the Hotel Business to 1750, The Industrial Revolution and the Hotel Business: 1750-1850, Economic Developments and the Hotel Business: 1850-1900, Critical Events and the Hotel Business: 1900-1945, The US Economic Structure and Hotel Business: 1945-1960, European Economic Structures and Hotel businesses: 1945-1960, The US Economic Structure and Hotel Business: 1960-1980, The European Economies and Hotel Businesses: 1960-1980, The US Hotel Business: 1980-2008, The British Hotel Business: 1980-2008, Continental European Hotel Businesses: 1980-2008, The Economic Ascent of the Hotel Business: Future Options, Hotel Supply and Demand Modelling.